The concept of intelligence. (1st March 2007) - Hand, Michael
Abstract : Analyses of the ordinary concept of intelligence are few and far between in philosophical literature. Such analyses as there have been in recent years are heavily influenced by Ryle's suggestion that to act intelligently is to act well or competently in a particular domain. Here I show that there are serious problems with Ryle's account and try to offer a more adequate analysis. I argue that to be intelligent is to have an aptitude for theory-intensive activities . I go on to explain why I think the ordinary concept of intelligence is a useful one for those professionally involved in the practice of education.